Meddling mansions - "Ghent, Jaz" (Hawthorn; Mimosa McGraw-Hill, 2007)
Hamish McCorkle has a very odd family. His grandmother is half-dragon, his father plays weird musical instruments, his mother yodels and Hamish himself can talk to birds. When the black sheep of the family, Hamish's Uncle Weaver, shows up to give Hamish a birthday present the family know he's up to no good. But what are his plans and what does he want with Hamish's sister Eugenie?
Donated by "Book Planet", Dated 18-4-2025.
Keywords: Children's stories, New Zealand